2014
DOI: 10.3390/ma7042833
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide—From Synthesis to Application: A Review

Abstract: Zinc oxide can be called a multifunctional material thanks to its unique physical and chemical properties. The first part of this paper presents the most important methods of preparation of ZnO divided into metallurgical and chemical methods. The mechanochemical process, controlled precipitation, sol-gel method, solvothermal and hydrothermal method, method using emulsion and microemulsion enviroment and other methods of obtaining zinc oxide were classified as chemical methods. In the next part of this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
996
0
24

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,017 publications
(1,038 citation statements)
references
References 201 publications
(184 reference statements)
18
996
0
24
Order By: Relevance
“…Оксид цинка является перспективным материалом для применения во многих областях, таких, как светоиз-лучающие диоды, пьезоэлектрические структуры, тон-копленочные транзисторы [1][2][3]. Различные сенсоры на основе ZnO [4][5][6] благодаря своей реакции на широкий круг веществ весьма перспективны для практических применений и интенсивно исследуются.…”
Section: Introductionunclassified
“…Оксид цинка является перспективным материалом для применения во многих областях, таких, как светоиз-лучающие диоды, пьезоэлектрические структуры, тон-копленочные транзисторы [1][2][3]. Различные сенсоры на основе ZnO [4][5][6] благодаря своей реакции на широкий круг веществ весьма перспективны для практических применений и интенсивно исследуются.…”
Section: Introductionunclassified
“…Radzimska and Jesionowski [25] reported that the particle size of ZnO-NPs synthesis using precipitation method is influenced by temperature, duration of calcination, and concentration of raw materials. In the sample T80C has a value of polydisperse index (PI) at 0.33.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…Both of commercials NPs having a particle size larger than T80C ZnO-NPs. Differences in shape, size and spatial structure of the particles may be caused by differences in the method of synthesis of ZnO-NPs [25].…”
Section: Morphology and Size Analysismentioning
confidence: 99%
“…The increase of the specific surface area and retardation of sintering of ZnO particles have been often achieved by the introduction of additional metal oxides. Modification of ZnO, especially for rubber production, has been often reached by functionalization of the surface of ZnO particles with silica, alumina, siloxane groups, deposition of organic and polymeric protecting layers [11]. In 1923, BASF introduced zinc oxide/chromium oxide catalysts for high-pressure methanol synthesis [12].…”
Section: Introductionmentioning
confidence: 99%